Production and reproduction performance of Red Sindhi cow - R. P. Jadhav; S. S. Kamble (Journal of Livestock Biodiversity, 2025)
The overall least square means for lactation length (LL), dry period (DP), calving interval (CI), lactation milk yield (LMY) and 300 days milk yield (300 DMY) in Red Sindhi cow were 310.876 ± 6.07 days, 81.99 ± 4.78 days, 392.86 ± 7.92 days, 1816.66 ± 38.95 kg and 1820.56 ± 34.18 kg respectively. The lactation length had significant effect over lactation milk yield, whereas, period of calving had significant effect over lactation milk yield and 300 days milk yield. The effect of age at first calving, season of calving, period of calving and lactation order over all the other traits under study was non significant.